Global Variations in the Time Delays Between Polar Ionospheric Heating and the Neutral Density Response. Issue 4 (7th April 2023) - Weimer, Daniel R.; Mehta, Piyush M.; Licata, R. J.; Tobiska, W. K.
Abstract: We present results from a study of the time lags between changes in the energy flow into the polar regions and the response of the thermosphere to the heating. Measurements of the neutral density from the Challenging Mini‐satellite Payload (CHAMP) and Gravity Recovery and Climate Experiment (GRACE) missions are used, along with calculations of the total Poynting flux entering the poles. During two major geomagnetic storms in 2003, these data show increased densities are first seen on the dayside edge of the auroral ovals after a surge in the energy input. At lower latitudes, the densities reach their peak values on the dayside earlier than on the night side. A puzzling response seen in the CHAMP measurements during the November 2003 storm was that the density at a fixed location near the "Harang discontinuity" remained at unusually low levels during three sequential orbit passes, while elsewhere the density increased. The entire database of measurements from the CHAMP and GRACE missions were used to derive maps of the density time lags across the globe. The maps show a large gradient between short and long time delays between 60° and 30° geographic latitude. They confirm the findings from the two storm periods, that near the equator, the density on the dayside responds earlier than on the nightside. The time lags are longest near 18–20 hr local time. The time lag maps could be applied to improve the accuracy of empirical thermosphere models, and developers of numerical models may find these results useful for comparisons with their calculations. Plain Language Summary: The interaction of the solar wind with the Earth's magnetosphere causes varying levels of heating in the ionosphere. This heating is produced by auroral currents at high latitudes, which in turn causes the density of the upper atmosphere to change. A topic of importance is to determine how rapidly the density can increase at different locations around the globe following a surge in the heating, which can be calculated from measurements of the solar wind velocity and embedded magnetic fields. This study used measurements of the atmospheric density on two satellite missions known as Challenging Mini‐satellite Payload and Gravity Recovery and Climate Experiment. The results show that the density increases first near the poles, and much longer at lower latitudes, as expected. The time lags between changes in the energy input and the density response have been determined for the first time on a global scale. Maps of the time lags are derived. Near the equator the lags are shorter near local noon, and longer before local midnight. The time lag maps can used to improve empirical and numerical models of the thermosphere. More accurate models are needed for more precise predictions of the drag that satellites will encounter, and the subsequent changes in their orbits. Key Points: Results show the time lags between auroral energy input and neutral density response, and how these lags vary across the globe Lag times are lowest in the polar regions, as expected, since this is where the heating occurs Near the equator the dayside responds earlier than on the nightside, and time lags are the longest near 18–20 hr local time